Glenohumeral Joint Preservation: A Review of Management Options for Young, Active Patients with Osteoarthritis - Olivier A. van der Meijden; Trevor R. Gaskill; Peter J. Millett (Advances in Orthopedics)
The management of osteoarthritis of the shoulder in young, active patients is a challenge, and the optimal treatment has yet to be completely established. Many of these patients wish to maintain a high level of activity, and arthroplasty may not be a practical treatment option. It is these patients who may be excellent candidates for joint-preservation procedures in an effort to avoid or delay joint replacement. Several palliative and restorative techniques are currently optional. Joint debridement has shown good results and a combination of arthroscopic debridement with a capsular release, humeral osteoplasty, and transcapsular axillary nerve decompression seems promising when humeral osteophytes are present. Currently, microfracture seems the most studied reparative treatment modality available. Other techniques, such as autologous chondrocyte implantation and osteochondral transfers, have reportedly shown potential but are currently mainly still investigational procedures. This paper gives an overview of the currently available joint preserving surgical techniques for glenohumeral osteoarthritis.